Needle or knife? The role of interventional radiology in managing uncontrolled gastrointestinal bleeding - Thomas G. Morgan; Tarryn Carlsson; Eric Loveday; Neil Collin; Graham Collin; Peter Mezes; Anne M. Pullyblank (International Journal of Gastrointestinal Intervention, 2021)
Background : : Increasingly interventional radiology has been used to stop uncontrolled gastrointestinal (GI) bleeding leading to a reduction in the requirement for surgical intervention. To examine the safety and efficacy of angiography and embolisation for the treatment of GI bleeding in a United Kingdom tertiary hospital. Methods : : This was a single-centre retrospective study of 112 procedures performed on 105 patients who underwent catheter angiography for GI bleeding over 7 years. Fifty procedures were for upper GI bleeding and 62 were for lower GI bleeding. Primary outcome was clinical success rate. Other measures were re-bleeding rates and 30-day mortality. Results : : In patients with upper GI bleeds, 71.6% of cases had a bleeding point that was identified at the time of initial catheter angiogram. Overall, the clinical success rate was 70.4% with a 20% 30-day mortality. Technical success with embolisation was 98% with no major complications. In patients with lower GI bleeds, 50% of cases had a bleeding point that was identified at the time of initial catheter angiogram. Overall clinical success rate was 83.0% with a 13.6% 30-day mortality. Technical success with embolisation was 100% with no major complications. Conclusion : : Catheter directed angiography and embolisation is safe and efficacious in patients with GI bleeding who have a positive computed tomography angiogram and should be considered as an alternative to surgery.